Intramembrane cleavage of AMA1 triggers Toxoplasma to switch from an invasive to a replicative mode. - Santos, J; Ferguson, D; Blackman, M; Soldati-Favre, D (2011)
Apicomplexan parasites invade host cells and immediately initiate cell division. The extracellular parasite discharges transmembrane proteins onto its surface to mediate motility and invasion. These are shed by intramembrane cleavage, a process associated with invasion but otherwise poorly understood. Functional analysis of Toxoplasma rhomboid 4, a surface intramembrane protease, by conditional overexpression of a catalytically inactive form produced a profound block in replication. This was completely rescued by expression of the cleaved cytoplasmic tail of Toxoplasma or Plasmodium apical membrane antigen 1 (AMA1). These results reveal an unexpected function for AMA1 in parasite replication and suggest that invasion proteins help to promote parasite switch from an invasive to a replicative mode.